2016
DOI: 10.1007/s10563-016-9215-9
|View full text |Cite
|
Sign up to set email alerts
|

Review of Acetic Acid Synthesis from Various Feedstocks Through Different Catalytic Processes

Abstract: Acetic acid (AA) has been largely used with a wide range of applications such as a raw material for a synthesis of vinyl acetate monomer, cellulose acetate or acetate anhydrate, acetate ester and a solvent for a synthesis of terephthalic acid and so on. The present paper briefly summarizes the commercialized chemical processes with their Rh or Ir-based catalytic systems in a liquid-phase carbonylation reaction such as Monsanto, Cativa and Acetica processes. In addition, some alternative catalytic systems such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 47 publications
(97 reference statements)
0
35
0
1
Order By: Relevance
“…It was demonstrated that 87.5 %a nd 80.4 %o fthem ethoxy groups in the kraft lignin and organosolv lignin could be transformed into acetic acid, respectively.T he reaction could be carried out at 120 8 8C, which is lower than the temperature required for the carbonylation of methanol to acetic acid (about 150-200 8 8C). [11] Kraft lignin, which is aby-product of paper industry,w as first studied. Thel ignin contained 11.0 wt %o fm ethoxy groups as determined by the iodine stoichiometry titration method, [12] and the apparatus and procedures are discussed in Supporting Information ( Figure S2 and Figure S3).…”
mentioning
confidence: 99%
“…It was demonstrated that 87.5 %a nd 80.4 %o fthem ethoxy groups in the kraft lignin and organosolv lignin could be transformed into acetic acid, respectively.T he reaction could be carried out at 120 8 8C, which is lower than the temperature required for the carbonylation of methanol to acetic acid (about 150-200 8 8C). [11] Kraft lignin, which is aby-product of paper industry,w as first studied. Thel ignin contained 11.0 wt %o fm ethoxy groups as determined by the iodine stoichiometry titration method, [12] and the apparatus and procedures are discussed in Supporting Information ( Figure S2 and Figure S3).…”
mentioning
confidence: 99%
“…Finally, the acyl‐species undergoes hydrogenation to ethanal which is reduced to ethanol. As the first three steps of the homologation reaction are identical with the carbonylation of methanol to acetic acid , the empirical knowledge of this process can be used to proceed the synthesis towards propanol(s) and butanol(s).…”
Section: Strategies Towards (Higher) Alcohols With Homogeneous Catalymentioning
confidence: 99%
“…The second approach is the reverse water-gas shift (RWGS) reaction of CO 2 or dry reforming of CH 4 to produce syngas, followed by the conversion of syngas to AA (Eqs. (2a-c)): [39][40][41] In the temperature range of 300-340 °C, the formation of AA and PA could be thermodynamically more feasible than the formation of methanol ( Supplementary Fig. 2).…”
Section: Introductionmentioning
confidence: 99%